Pressure dependence of structural, elastic and electronic properties of α-Al2O3: first-principles calculations - Liu, Qi-Jun; Liu, Zheng-Tang (Penerbit Universiti Kebangsaan Malaysia, 2016)
The first-principles calculations were performed to investigate the structural, elastic, mechanical and electronic properties of α-Al2O3 at applied pressure up to 50 GPa. The obtained ground state properties were in agreement with previous experimental and theoretical data. The elastic constants, bulk modulus, shear modulus, Young’s modulus and anisotropy have been calculated as pressure increased. It was found that there was a brittle-ductile transition at about 23.2 GPa. The increasing ratio Ba /Bc with pressure indicates the weakening chemical bonding and the increasing anisotropy in this compound. The electronic structures were also calculated, which shows that band gaps increase monotonically. The population analysis showed the charge transfer was mainly between Al-3s and O-2p as pressure increased.